Measuring pathology using the PANSS across diagnoses: Inconsistency of the positive symptom domain across schizophrenia, schizoaffective, and bipolar disorder. (December 2017) - Anderson, Ariana E.; Mansolf, Maxwell; Reise, Steven P.; Savitz, Adam; Salvadore, Giacomo; Li, Qingqin; Bilder, Robert M.
Abstract: Although the Positive and Negative Syndrome Scale (PANSS) was developed for use in schizophrenia (SZ), antipsychotic drug trials use the PANSS to measure symptom change also for bipolar (BP) and schizoaffective (SA) disorder, extending beyond its original indications. If the dimensions measured by the PANSS are different across diagnoses, then the same score change for the same drug condition may have different meanings depending on which group is being studied. Here, we evaluated whether the factor structure in the PANSS was consistent across schizophrenia ( n = 3647), bipolar disorder ( n = 858), and schizoaffective disorder ( n = 592). Along with congruency coefficients, Hancock's H, and Jaccard indices, we used target rotations and statistical tests of invariance based on confirmatory factor models. We found the five symptom dimensions measured by the 30-item PANSS did not generalize well to schizoaffective and bipolar disorders. A model based on an 18-item version of the PANSS generalized better across SZ and BP groups, but significant problems remained in generalizing some of the factors to the SA sample. Schizophrenia and bipolar disorder showed greater similarity in factor structure than did schizophrenia and schizoaffective disorder. The Anxiety/Depression factor was the most consistent across disorders, while the Positive factor was the least consistent. Highlights: The five dimensions of the 30-item PANSS vary across diagnoses. Schizophrenia factor structure was more similar to bipolar disorder than to schizoaffective disorder. The Positive symptom domain varied most across diagnoses. The Anxiety symptom domain was the most consistent across diagnoses. The 18-item PANSS was more stable than the 30-item PANSS across diagnoses.